Cryopreservation of cord blood CD34+ cells before or after thrombopoietin expansion differentially affects early platelet recovery in NOD SCID mice. Issue 7 (27th February 2015) - van Hensbergen, Yvette; van der Garde, Mark; Brand, Anneke; Slot, Manon C.; de Graaf‐Dijkstra, Alice; Watt, Suzanne; Zwaginga, Jaap Jan
<x xml:space="preserve">Abstract</x> BACKGROUND Expansion of human cord blood (CB) CD34+ cells with thrombopoietin (TPO) can accelerate delayed platelet (PLT) recovery after transplantation into immunodeficient mice. Clinical implementation, however, will depend on practical and effective protocols. The best timing of TPO expansion in relation to cryopreservation in this respect is unknown. STUDY DESIGN AND METHODS In this study, we evaluated whether the order of cryopreservation and TPO expansion affected the expansion rate and numbers of clonogenic hematopoietic progenitor cells in vitro or PLT and longer‐term hematopoietic repopulation in NOD SCID mice in vivo. RESULTS Our results demonstrate higher expansion rates and the generation of higher numbers of multilineage and megakaryocytic progenitors (granulocyte, erythrocyte, monocyte, megakaryocyte colony‐forming units and megakaryocyte colony‐forming units) in vitro when freshly isolated CB CD34+ cells are first cultured with TPO and then cryopreserved and thawed as compared to TPO expansion after CD34+ cell cryopreservation. In contrast, the cells produced with the latter strategy showed higher expression of CD62L and a superior stromal cell–derived factor‐1α–mediated migration. This might play a role in an also observed superior early PLT recovery after transplantation of these cells into NOD SCID mice. The hematopoietic engraftment in the marrow 6 weeks after transplantation was not different between the two strategies. CONCLUSION Although TPO expansion before cryopreservation would yield higher nucleated cell and clonogenic myeloid and megakaryocyte cell numbers and enable earlier availability, CB TPO expansion after cryopreservation is likely to be clinically more effective, despite the lower number of cells obtained after expansion. Moreover, the latter strategy is logistically more feasible.